Utilizing Narrative Text as a Means of Incorporating Literature into English Language Teaching to Enhance Students' Listening and Speaking Skills - Khoir, Azizatul; Jessenianta, Aurel Keisha; Rohmana, Wahyu Indah Mala (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
This study explores the efficacy of using narrative texts to enhance students' speaking and listening skills in English Language Teaching (ELT). Employing a qualitative descriptive method, the research involved interviews with English teachers and two junior high school students, investigating the integration of narrative texts in ELT for bolstering listening and speaking proficiencies. The primary objective was to identify obstacles encountered by educators and students when employing narrative texts as a tool to cultivate speaking and listening skills. Findings indicate that integrating narrative texts presents a promising pedagogical approach, fostering collaborative learning, critical thinking, and enhanced linguistic abilities. Despite challenges, such as instructional refinement and overcoming learning obstacles, this research underscores the immense potential of narrative texts in advancing students' language proficiency. Sustained efforts in tailoring instructional strategies and providing support are crucial to maximizing the benefits of utilizing narrative texts in ELT, paving the way for improved language acquisition.